2019
DOI: 10.19102/icrm.2019.100304
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Important Drug–Drug Interactions Between Antiarrhythmic Drugs and Anticoagulants

Abstract: Until the last decade, vitamin K antagonists (VKAs) were the only agents available for oral anticoagulation. Although effective and accessible, their use was complicated by a narrow therapeutic window, the need for regular monitoring of the international normalized ratio, and an associated susceptibility to interactions with both food and numerous medications. Furthermore, the onset of action was delayed, often requiring bridging with intravenous agents. In more recent years, we have enjoyed the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…128 Quinidine is also a weak inhibitor of CYP3A4 and INR should be monitored more frequently when quinidine is initiated in the setting of chronic warfarin use. 14,147…”
Section: Oral Anticoagulants and Antiarrhythmic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…128 Quinidine is also a weak inhibitor of CYP3A4 and INR should be monitored more frequently when quinidine is initiated in the setting of chronic warfarin use. 14,147…”
Section: Oral Anticoagulants and Antiarrhythmic Drugsmentioning
confidence: 99%
“…1 This increase in plasma concentration can be tempered by administering dronedarone 2 hours after DOAC administration, but this combination should generally be avoided with all DOACs. 128,147 While a study reported no clinically significant elevation in INR in patients taking warfarin who were initiated on dronedarone, a moderate CYP3A4 inhibitor, cases of dronedarone-associated increases in INR have been reported. 148,149…”
Section: Oral Anticoagulants and Antiarrhythmic Drugsmentioning
confidence: 99%
“…64 Amiodarone can also increase plasma dabigatran and rivaroxaban concentrations, especially in patients with kidney disease. 163–165…”
Section: P-glycoproteinmentioning
confidence: 99%
“…После всасывания ПОАК попадают в центральное кровообращение и подвергаются различным степеням метаболизма через систему печеночного цитохрома P450 3A4 и выводятся с различной скоростью с мочой и стулом [18]. [20]. Соталол не метаболизируется и вместо этого элиминируется нормальными почками без изменений [21].…”
Section: транспортная система P-gp (гликопротеины проницаемости или белок множественной лекарственной резистентности)unclassified